Remagnetization of Marcellus Formation in the Plateau Province of the Appalachian Basin - Steullet, Alex Kayla; Elmore, R. Douglas; Hamilton, Matt; Heij, Gerhard (Frontiers in Earth Science, 2019)
An integrated paleomagnetic, magnetic fabric, and petrographic study of two cores (EC: oriented; DB: unoriented) in the Devonian Marcellus Formation from the Plateau Province (PA) indicates the presence of chemical remanent magnetizations (CRMs) and extensive diagenetic alteration. Anisotropy of magnetic susceptibility results indicate a predominately oblate fabric. Some specimens contain a prolate fabric that is interpreted as diagenetically altered. A well-developed viscous magnetization, possibly contaminated by a drilling induced component, is not present in either core, and cannot be used for orientation. An intermediate temperature component with steep down inclinations (ITN) is removed in both cores below ~ 300°C. Specimens in DB also contain a component with steep up inclinations (ITR) that is removed between 300 and 440°C. The ITN is interpreted to reside in magnetite and/or possibly pyrrhotite, and the ITR resides in magnetite. The ITN could be a reversal of ITR, acquired in the Cretaceous to Cenozoic based on a comparison with the expected inclinations. Alternatively, the ITN could be a contaminated by a Brunhes viscous magnetization. Specimens from both cores contain a characteristic remanent magnetization (ChRM) with shallow inclinations that is removed by 500°C in DB and 460°C in EC, and is interpreted to reside in magnetite. The DB ChRM has an inclination of -9.0°, which corresponds to a range of ages between 310-225 Ma based on the expected inclinations. The ChRM in EC has streaked declinations, which may have been caused by core barrel rotation. Shallow inclinations (- 3.7°) in this core suggest a range of acquisition from 305-230 Ma. Rock magnetic data are consistent with the presence of magnetite but provide conflicting evidence for pyrrhotite. The ChRM in DB is interpreted as a CRM whereas the ChRM in EC could be thermoviscous in origin. Diagenetic studies indicate a complex paragenesis with authigenic minerals such as barite, sphalerite, baroque dolomite, and sylvite suggestive of alteration by external fluids. The presence of the CRM in highly altered zones suggests it is related to alteration by external fluids, although its presence in other facies suggests that burial diagenetic processes could also be a cause of remagnetization.